INTEGRATION SYSTEM OF CAD/CAM IN MACHINARY PROCESS USING WIRE-EDM - Domi Kamsyah; Ari Kurniadi; Benny Haddli Irawan; Rahman Hakim; Saiful Arif (Jurnal Teknologi dan Riset Terapan (JATRA), 2021)
Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) are usually used to draw sketches and model manufacturing work processes on machines that operate using computer numerical control (CNC). To communicate with each other CAD and CAM must have the same format, the drawings produced by CAD must the same format to be run on the CAM. In this study, product images will be created using Autocad software and it will run on the Fikus VisualCAM 19 software to visualize the tool pathway. The program is created to run a CNC machine and the resulting product will check the conformity of its dimensions and geometry. The results obtained are that the images generated from the AutoCAD software can run well on the Fikus VisualCAM 19 software. The program in the form of NC code generated by AutoCAD and Fikus VisualCAM19 software can be run properly by a CNC wire-cutting EDM machine, this can be seen from the product results that match the dimensions and geometry.